Vapor de transporte madeira: arqueologia marítima histórica da revolta da armada de 1893 - Santos, Luis Felipe Freire Dantas (2020)
This research aims to discuss the data produced by the project of the Casco de Mocanguê I Archaeological Site, an underwater archaeological research developed in Guanabara Bay, in the city of Niterói-RJ, within the field of contract archaeology. Through the analysis of the political context in which the project was developed, we will discuss the case study from the perspective of maritime archeology with a critical bias, where we will present the main issues surrounding the process of building archaeological knowledge, and also analyzing the Brazilian Naval Revolts as an internal conflict that occurred in the first years of the Brazilian republic, promoted by oligarchic/military sectors that wanted to seize the current power, through a political coup through the implantation of State Terrorism. In the course of Brazilian republican politics, we have often seen these movements repeat themselves, sometimes with the establishment of authoritarian regimes. Almost always, the materiality related to these events is deliberately "erased". In the case of the Brazilian Naval Revolts, the possible identification of archaeological sites of shipwrecks brings up an extremely necessary and current archaeological and political theme, opening paths and possibilities for future research in similar contexts, inside and outside the contract archaeology. The survey of the wreck site of the vessel Madeira Steamship (Casco de Mocanguê I) was demanded of an environmental and patrimonial issue, as it was identified during the execution of a dredging project, carried out in the navigation channel near the Mocanguê island. Through geophysical surveys, direct investigation and historical research, the identity of the collapsed hull and the partial rescue of part of its structures were carried out, using the Appendix of the Unesco Convention for the Protection of the Underwater Cultural Heritage of 2001 as a reference. using different technologies in the archaeological record process, we generate a range of data on the context formed by the remains of the vessel, mitigating the problems caused by the conditions of the area and the dynamics of the research, creating means that facilitate the diffusion and popularization of the archaeological knowledge built on the submerged site, as well as creating ways to deepen the archaeological information produced even outside the scope of contract archaeology, a challenge started with the present thesis.